The J-shaped relationship between serum osmolality and all-cause mortality in critically ill patients with myocardial infarction: a retrospective cohort study - Gui, Long; Cao, Heshan; Zheng, Min; Pan, Yu; Ning, Chengdong; Cheng, Mingjin (Frontiers in Endocrinology, 2025)
BackgroundSerum osmolality (SOSM) is an indicator of hydration status and is associated with the prognosis of various cardiovascular diseases. This study investigated the association between SOSM and all-cause mortality in critically ill patients with myocardial infarction (MI).MethodsThis retrospective cohort study utilized data from the Medical Information for Intensive Care-IV (MIMIC-IV) database, including critically ill patients with a primary diagnosis of MI. Patients were categorized into tertile groups based on the SOSM levels. Kaplan-Meier (K-M) survival analysis, multiple Cox regression models, restricted cubic spline (RCS) analysis, and threshold effect analysis were used to investigate the nonlinear relationship between all-cause mortality in critically ill patients with MI and SOSM.ResultsA total of 5354 patients with MI were included. K-M survival analysis showed that the survival rate of the high SOSM group was significantly lower than that of the other groups, which was consistent with the results after IPTW correction (log-rank P<0.05). Multiple Cox regression confirmed that patients with high SOSM had significantly increased risk of death at 30-day [HR, 1.45 (95% CI 1.21–1.73) P<0.001], 180-day [HR, 1.32 (95% CI 1.15-1.53) P<0.001], and 365-day [HR, 1.31(95% CI1.15-1.49) P<0.001]. RCS analysis and threshold effect analysis showed a J-shaped relationship between SOSM and mortality risk, and the minimum threshold of SOSM was 286.28 mmol/L.ConclusionsThis study revealed a J-shaped relationship between SOSM and all-cause mortality in critically ill MI patients, suggesting its potential as a prognostic marker for risk stratification.